Penanaman Nilai-Nilai Karakter Dalam Kurikulum 2013 Pada Pelajaran Pendidikan Agama Islam - Arie Bastian Hadinata (Jurnal Penelitian Medan Agama, 2020)
This paper is motivated by the number of general public complaining about the decline in ethics and manners of teenagers. The decrease in the ethics of teenagers resulted in frequent juvenile delinquency in Indonesia. The decline of the nation's morale, especially youth due to the weakening of cultural and character education both integrated in formal education and non-formal education. Many factors that can cause the emergence of deviant behavior among students, including the lack of a strong grip on religion, the lack of effective moral or character coaching by families, schools and communities, the rapid flow of materialistic, hedonistic, and sectarian culture, and the lack of a genuine willingness of the government to conduct coaching on the morals of the nation, Through literature studies (library research) the author will present the terms of character in Islamic education , so that problems with children will be found, with it will know the values of character taught in Islamic education and also know the problems of planting character values to students.